Active Virtues - Michael D. Gilbert; Mauricio A. Guim (Washington University Law Review, 2021)
Constitutional theory has long been influenced by the idea that the Supreme Court exercises “passive virtues,” avoiding politically divisive cases that threaten its legitimacy. The Article inverts the logic. Supreme Court Justices (and other judges too) do more than avoid divisive cases that could weaken the Court. They seek “unity” cases—meaning cases where law and politics align—that could strengthen the Court. When judges seek unity cases to enhance their legitimacy, they exercise active virtues. We develop the theory of active virtues and demonstrate its use. Our case studies come from the U.S. Supreme Court and tribunals worldwide, and they involve issues like voting, piracy, and police. Following the case studies, we situate active virtues in a broader theory of judicial power. According to our theory, courts balance divisive and unity cases like investors balance stocks and bonds. This portfolio theory of judicial power illuminates a range of topics, including docket control, activism, the counter-majoritarian difficulty, and the rule of law. Recognizing active virtues may have implications for today’s Supreme Court, which faces a legitimacy crisis.
Keywords: Supreme Court; Passive virtues; Active virtues; Judicial legitimacy; Judges; Divisive cases; Unity cases